The Economic Contribution of Culture - Yves Jauneau
In 2011, cultural industries had a total production of 85 billion euros with an added value of 40 billion euros. Cultural production is divided and shared between a merchantable amount of 69 billion euros from the sale of companies' cultural goods and services, and a non-merchantable amount of 16 billion euros, which corresponds, by convention, to the production costs of departments, public institutions and associations in the cultural sector. The direct economic impact of culture, measured as the relationship between the added value of cultural industries and that of all industries, was 2.2% in 2011. It did not take into account the indirect or induced economic benefits resulting from culture (tourism, for example). Until 2003, the direct economic impact developing the value of culture has increased. However, it has been falling since 2004, which is mainly attributed to the marked decline in activity in certain cultural industries (publishing, the press, record). In 2011, the audio-visual industry (radio, cinema, television, video, record) contributed to one quarter of added cultural value. The performing arts and heritage, predominantly non-merchantable industries, contributed to 18% and 11% of added value respectively. The progress made during the last fifteen years in the share price in terms of value of the performing arts is mainly down to the rising prices in this industry. In contrast, books and the press only contributed to 15% of added cultural value in 2011, versus 26% in 1995. Other cultural industries (advertising agencies, architecture, the visual arts, cultural education) contributed, as a whole, to one third of added cultural value.